How Does Ores and Metal Exports, Fuel Exports and Inflation Affect Economic Growth in Indonesia? An Autoregressive Distributed Lag Approach - Soeparno, Wahyu Sugeng Imam; Hasyim, Sirojuzilam; Rusydiana, Aam Slamet; Nasution, Inggrita Gusti Sari; Anggia, Yola (International Journal of Economics and Financial Issues, 2025)
The study investigates the impact of ores and metal exports, fuel exports, and inflation on economic growth using the Autoregressive Distributed Lag (ARDL) approach in Indonesia. Indonesia's economy, significantly dependent on its inflation and natural resources, particularly ores and metals, and fuels, has experienced varied impacts on growth due to these factors. This research aims to analyze the long-term and short-term dynamics between these variables and economic growth. The analysis employs annual time series data from 1990 to 2022, focusing on GDP growth, inflation rates, ore and metal exports, and fuel exports. The ARDL approach is chosen for its ability to handle small sample sizes and mixed integration orders of variables. This method provides a comprehensive examination of both long-term equilibrium relationships and short-term adjustments. The findings reveal a positive but statistically insignificant long-term impact of ores and metal exports on GDP growth. In contrast, fuel exports show a significant positive long-term effect on economic growth. However, the potential for negative long-term impacts due to over-reliance on fuel exports is noted. Inflation demonstrates a complex relationship with economic growth in the long-term. Short-term analysis indicates that both ore and metal exports and fuel exports positively affect GDP growth. The short-term negative impact of inflation is significant. This study contributes to the literature by providing empirical evidence on the critical roles of natural resource exports and inflation in shaping Indonesia's economic growth. The findings offer valuable insights for policymakers aiming to develop sustainable economic strategies that mitigate risks associated with resource dependency and inflation, thereby fostering long-term economic stability and growth.